Investigation of Ceramic Dental Prostheses based on ZrSiO4 2013; Glass Composites Fabricated by Indirect Additive Manufacturing (Global Journal of Medical Research, 2020)
Technologies for dental prosthesis and restoration have been developed during the past years Despite the advantages of additive manufacturing CAD CAM technologies lead prostheses fabrication Therefore the main goal of this work is to investigate the fabrication of dental prosthesis based on ZrSiO4-glass composites applying the indirect fused deposition modelling In order to achieve this goal we used filaments filled by 90 of ZrSiO4 and 50 m glass spheres in order to fabricate prosthesis We also applied multivariable approach to scan the feasibility of the proposed process Holding temperature holding time heating rate and cooling rate were considered the control factors while shrinkage flexural strength process feasibility were the study responses It was possible to see the proposal feasibility for holding temperatures between 700 and 800 C and holding time between 1 and 4 hours Additionally the materials flexural strength was found between 25 and 85MPa while shrinkage fluctuated between 10 and 25
Keywords: FDM ceramic sintering; additive manufacturing; ceramics